KPT-330, a potent and selective exportin-1 (XPO-1) inhibitor, shows antitumor effects modulating the expression of cyclin D1 and surviving in prostate cancer models. Issue 1 (December 2015) - Gravina, Giovanni; Mancini, Andrea; Sanita, Patrizia; Vitale, Flora; Marampon, Francesco; Ventura, Luca; Landesman, Yosef; McCauley, Dilara; Kauffman, Michael; Shacham, Sharon; Festuccia, Claudio
Abstract Background and aims Increased expression of Chromosome Region Maintenance (CRM-1)/exportin-1 (XPO-1) has been correlated with poor prognosis in several aggressive tumors, making it an interesting therapeutic target. Selective Inhibitor of Nuclear Export (SINE) compounds bind to XPO-1 and block its ability to export cargo proteins. Here, we investigated the effects of a new class of SINE compounds in models of prostate cancer. Material and methods We evaluated the expression of XPO-1 in human prostate cancer tissues and cell lines. Next, six SINE (KPT-127, KPT-185, KPT-205, KPT-225, KPT-251 and KPT-330) compounds having different potency with broad-spectrum, tumor-selective cytotoxicity, tolerability and pharmacokinetic profiles were tested in a panel of prostate cancer cells representing distinct differentiation/progression states of disease and genotypes. Two SINE candidates for clinical trials (KPT-251 and KPT-330) were also tested in vivo in three cell models of aggressive prostate cancer engrafted in male nude mice. Results and conclusions XPO-1 is overexpressed in prostate cancer compared to normal or hyperplastic tissues. Increased XPO-1 expression, mainly in the nuclear compartment, was associated with increased Gleason score and bone metastatic potential supporting the use of SINEs in advanced prostate cancer. SINE compounds inhibited proliferation and promoted apoptosis of tumor cells, but did not affect immortalized non-transformed prostate epithelial cells. Nuclei from SINE treated cells showed increased protein localization of XPO-1, survivin and cyclin D1 followed by degradation of these proteins leading to cell cycle arrest and apoptosis. Oral administration of KPT-251 and KPT-330 in PC3, DU145 and 22rv1 tumor-bearing nude mice reduced tumor cell proliferation, angiogenesis and induced apoptosis. Our results provide supportive evidence for the therapeutic use of SINE compounds in advanced/castration resistant prostate cancers and warrants further clinical investigation.